Image 1_A comprehensive longitudinal analysis of the cellular immune response specific to the spike protein in healthcare workers vaccinated against SARS-CoV-2– ORCHESTRA Project.pdf - Stefano Ugel (7402733) (2025)
Introduction The long-term dynamics of T-cell immunity following SARS-CoV-2 vaccination, essential for durable protection, remain incompletely understood. This study, therefore, aimed to investigate the kinetics and persistence of spike-specific T-cell responses in vaccinated healthcare workers. Methods Within the framework of the ORCHESTRA Project, we conducted a longitudinal study on the kinetics and persistence of CD4+ and CD8+ T cell immunity in healthcare workers (n=305) from four hospitals and public health centers across two European countries who received either 2 or 3 doses of an mRNA vaccine, with or without prior SARS-CoV-2 infection. Specifically, the anti-spike adaptive immune cellular response was evaluated, focusing on its crosstalk with the B cell response as measured by serology. Circulating cellular adaptive immune cells were extensively analyzed using flow cytometry to assess pro-inflammatory cytokine production (TNF-α, IFN-γ, IL-2), functional activation (CD154), and memory differentiation (CD45RO). Results Our findings show that anti-spike T cell reactivity is not influenced by age, with the only exception of a weak positive correlation with spike-specific CD8+CD45RO+ T lymphocytes (Spearman’s rho = 0.34, p<0.001), and an equally weak negative correlation with CD8+TNF+ (Spearman’s rho = -0.23, p<0.01). Other variables, such as gender and job category, did not significantly impact the vaccine-induced, anti-spike T cell immune response. Discussion No distinct relationship between CD4+ and CD8+ T cell subsets was observed post-vaccination. However, specific dynamic changes in vaccine-induced T cells were identified showing clear dose- and time-dependence. Finally, the median level of CD8+CD154+ lymphocytes, indicative of activated T cells, was significantly associated with infection incidence and may represent a reliable predictive biomarker. This study provides evidence that the vaccine-induced anti-spike cellular immune response should be considered when making vaccination decisions, as it has predictive value for infection risk.